Preparation and Properties of Olive Oil Microcapsules (Journal of Fiber Bioengineering and Informatics, 2012)
In this paper, microcapsules were produced by complex coacervation using gelatin and acacia as wallmaterials and olive oil as the core substance. Process parameters, such as the dosage of the crosslinker,concentration of the wall materials, pH Value and the ratio between core and wall materials were analyzedin detail. Moreover, crosslinking degree of wall materials was more important in obtaining good slowrelease microcapsules. The morphology and particle size distribution of the microcapsules were analyzedby scanning electron microscope and laser particle size analyzer. The oil content and the release rate ofthe olive oil were also studied. In order to obtain microcapsules with good mobility and dispersal, a spraydrying process was used to dry the product. The olive oil microcapsules were obtained with particle sizeof 3 ∼ 8 μm, and an oil content of about 60%. The optimum process parameters were as follows:dosage ofthe cross linking agent was 3 ml, the concentration of wall materials was 3%, the pH value of coacervationwas 4.0 and the ratio of core/wall material was 1:1. Olive oil microcapsules prepared with these optimalprocess conditions had good disperse effect and high encapsulation efficiency.
Keywords: Gelatin; Microcapsules; Complex Coacervation; Olive Oil; Arabic Gum